Application of the Discovery Learning Teaching Model in Mathematics Subjects - Marina Rahmayanti (HM Publisher, 2021)
Discovery learning itself occurs when individuals are involved, especially in using mental processes to find some concepts and principles. By using this model, students are required to carry out various activities to collect information, compare, categorize, analyze, integrate, reorganize materials and make their conclusions. In the discovery learning model, students are expected to be more active by processing information and mathematical concepts. Students are also able to make conclusions from the learning material that has been taught. This literature review was to obtain an overview of discovery learning models. From these results, it can be concluded that student learning achievement with a model of discovery learning differs significantly where the student learning achievement with a discovery learning model is higher than with the direct instruction model.